Accuracy of emergency physician–performed ultrasonography in the diagnosis of deep-vein thrombosis - Pomero, Fulvio; Dentali, Francesco; Borretta, Valentina; Bonzini, Matteo; Melchio, Remo; Douketis, James D.; Fenoglio, Luigi Maria (Thrombosis and Haemostasis, 2013)
Duplex ultrasound is the first-line diagnostic test for detecting lower limb deep-vein thrombosis (DVT) but it is time consuming, requires patient transport, and cannot be interpreted by most physicians. The accuracy of emergency physician–performed ultrasound (EPPU) for the diagnosis of DVT, when performed at the bedside, is unclear. We did a systematic review and meta-analysis of the literature, aiming to provide reliable data on the accuracy of EPPU in the diagnosis of DVT. The MEDLINE and EMBASE databases (up to August 2012) were systematically searched for studies evaluating the accuracy of EPPU compared to either colour-flow duplex ultrasound performed by a radiology department or vascular laboratory, or to angiography, in the diagnosis of DVT. Weighted mean sensitivity and specificity and associated 95% confidence intervals (CIs) were calculated using a bivariate random-effects regression approach. There were 16 studies included, with 2,379 patients. The pooled prevalence of DVT was 23.1% (498 in 2,379 patients), ranging from 7.4% to 47.3%. Using the bivariate approach, the weighted mean sensitivity of EPPU compared to the reference imaging test was 96.1% (95%CI 90.6–98.5%), and with a weighted mean specificity of 96.8% (95%CI:94.6–98.1%). Our findings suggest that EPPU may be useful in the management of patients with suspected DVT. Future prospective studies are warranted to confirm these findings.
Keywords: Ultrasound; deep-vein thrombosis; emergency physician